2018
DOI: 10.1093/jbcr/iry009
|View full text |Cite
|
Sign up to set email alerts
|

An Overview of the Use of Bromelain-Based Enzymatic Debridement (Nexobrid®) in Deep Partial and Full Thickness Burns: Appraising the Evidence

Abstract: Recent introduction of rapid bromelain-based enzymatic debridement has been increasingly popular in its use in nonsurgical debridement in deep partial and full thickness burns. We designed this study to evaluate the evidence suggested by current studies on the perceived benefits of using Nexobrid® compared with traditional surgical standard of care in burns wound debridement. A comprehensive search on electronic databases Pubmed, Embase, and Web of Science was done to identify studies published between 1986 an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
23
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 35 publications
(28 citation statements)
references
References 27 publications
1
23
0
1
Order By: Relevance
“…More RCTs are needed to establish its efficacy and feasibility before it is broadly accepted. 52,55 Collagenase Collagenase ointment generally refers to a collagenase proteolytic mixture derived from Clostridium histolyticum, although collagenase mixtures derived from other bacterial sources such as Streptomyces also exist. 56,57 Because collagenase is specific to collagen, a protein comprising up to 75% of the dermis, it is considered a "selective" debriding agent.…”
Section: Bromelain-based Enzymatic Agentsmentioning
confidence: 99%
“…More RCTs are needed to establish its efficacy and feasibility before it is broadly accepted. 52,55 Collagenase Collagenase ointment generally refers to a collagenase proteolytic mixture derived from Clostridium histolyticum, although collagenase mixtures derived from other bacterial sources such as Streptomyces also exist. 56,57 Because collagenase is specific to collagen, a protein comprising up to 75% of the dermis, it is considered a "selective" debriding agent.…”
Section: Bromelain-based Enzymatic Agentsmentioning
confidence: 99%
“…Despite the growing experience, the literature offers seven publications on studies with a high level of evidence proving ED' s advantages with certain issues over standard of care (SOC), which is remarkable for literature in burns. Loo et al [16] investigated literature on ED from 1986 to 2017 and reported seven prospective studies including four randomized controlled trials in a recent review. The largest available randomized-control trial by Rosenberg et al [5] compared 74 cases of ED with 81 cases treated by SOC and could show a significant shorter time to complete eschar removal, a lower number of wounds requiring surgical excision and STSG as well as a significant lower blood loss in in the ED group.…”
Section: Discussionmentioning
confidence: 99%
“…It is associated with a reduced time to complete debridement, reduced need for surgery, reduced area of burns excised, and reduced need for autografting. 179 Chemical debridement is far less painful than sharp debridement, so a general anesthetic is usually avoided. However, its use is associated with procedural pain therefore local or regional anesthesia and/or pre-emptive analgesia are required.…”
Section: Surgical Managementmentioning
confidence: 99%